Trans-umbilical Single-Site Plus One Robotic Assisted Surgery for Choledochal Cyst in Children, a Comparing to Laparoscope-Assisted Procedure - Lin, Shan; Chen, Jianglong; Tang, Kunbin; He, Yufeng; Xu, Xinru; Xu, Di (Frontiers in Pediatrics, 2022)
Objective We introduce the trans-umbilical single-site plus one robotic-assisted surgery for the treatment of pediatric choledochal cyst. Compare the intraoperative and postoperative outcomes between the new method and traditional laparoscopy-assisted procedure. Method We retrospectively analyzed the clinical data of 51 children diagnosed with choledochal cysts and received surgery from June 2019 to December 2020 at our department. About 24 patients who underwent the robot-assisted procedure were selected as the R group, and 27 patients who underwent the laparoscope-assisted procedure were selected as the L group. We compare the intraoperative and postoperative outcomes between the two groups. Result No significant differences were found in demographic information between the two groups (P > 0.05). The median total operative time, median port/trocar installation time, and median wound suture time of the R group were a little longer than the L group (217.63 ± 5.90 vs. 199.37 ± 5.13 min; 30.71 ± 3.18 vs. 6.11 ± 1.15 min; 30.79 ± 1.82 vs. 20.40 ± 3.12 min, respectively; P < 0.001). However, the R group had shorter choledochal cyst excision time and mean hepaticojejunostomy anastomosis time than the L group (52.04 ± 2.74 vs. 59.26 ± 3.23 min; 52.42 ± 2.72 vs. 60.63 ± 3.30 min, respectively, P < 0.001). The mean extracorporeal Roux-y jejunojejunostomy time of two groups has no remarkable difference (P > 0.05). The R group also had less mean volume of blood loss (7.04 ± 1.16 vs. 29.04 ± 18.21 mL; P < 0.001). The R group had a shorter indwelling time of gastric tube, anal exhaust time, water feeding time, solids feeding time, and hospital stay time than the L group (P < 0.05). The R group had a lower early complication rate than the L group (4.2 vs. 29.63%; P = 0.026). No statistical differences were identified between the two groups in late or any single complication (0.00 vs. 11.11%; P > 0.05). Conclusions A resection of the choledochal cyst and a Roux-en-Y hepaticojejunostomy can be performed much more precisely by single-site plus one robotic-assisted surgery. Patients can achieve rapid recovery, and the umbilical incision is more concealed and beautiful. Combing the experience of single-site surgery with robot-assisted surgery, the operators can implement the technique in children safely and feasibly.